Personalized persistent atrial fibrillation ablation guided by left atrial wall thickness: a multicenter study. (19th May 2022) - Falasconi, G; Penela, D; Jauregui, B; Soto-Iglesias, D; Teres, C; Ordonez, A; San Antonio, R; Viveros, D; Bellido, A; Scherer, C; Marti, J; Sabate, X; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) has been proven to be effective in treating persistent atrial fibrillation (PeAF), although long-term ablation outcomes have been significantly less satisfactory than in paroxysmal AF (1). A recent personalized PVI approach, aiming for contiguous lesions with ablation index (AI) titration according to the local left atrial wall thickness (LAWT) as per multidetector cardiac tomography (MDCT), has demonstrated to achieve an arrhythmia-free survival > 95% at 12 months in patients with paroxysmal AF (2). Purpose: We sought to investigate the safety and clinical outcomes of this personalized PVI approach guided by LAWT in patients with PeAF. Methods: Consecutive patients referred for PeAF first ablation were prospectively enrolled from three referral centers. PeAF was defined in the presence of at least one AF episode sustained beyond 7 days. LAWT three-dimensional maps were obtained from MDCT and integrated into the navigation system. LAWT was categorized into 1 mm layers and AI was titrated to the LAWT. The ablation line was personalized to avoid thicker regions (Figure 1) while encircling PV antrum. Follow-up was scheduled at 1, 3, 6, and every 12-months thereafter. Results: One hundred twenty-seven patients [89 (70.6%) male, age 64 ± 10 years] were included. 68 (60.7%) patients were hypertensive, 10 (18%) patients suffered of type 2 diabetes, and mean CHA2DS2-VASc score was 2.3 ± 2.1. Mean procedure time was 61 ± 20 minutes and mean fluoroscopy time was 1.3 ± 2.2 minutes. Radiofrequency (RF) time was 9.0 ± 2.3 minutes for the right pulmonary veins with a first-pass isolation in 109 (85.8%) patients and 7.6 ± 1.9 minutes for the left pulmonary veins with first-pass in 110 (86.6%). No major complication occurred. The rate of survival free from AF recurrences at a mean follow-up of 12 ± 6 months was 82% (Figure 2). Conclusions: Personalized Persistent AF ablation by wide circle PV isolation guided by LAWT, proved to be safe and highly efficient, requiring a low amount of RF delivery, procedure time, and fluoroscopy use, while obtaining a high rate of first-pass isolation and of freedom from AF recurrences.